Rogue cops among rogues trolls and trolling in social networking sites - Escartin, Maria Corinna Priscila D. (Philippine Sociological Review, 2015)
Contents reflecting sarcasm, insults and provocation have been known to bombard online fora, Facebook pages, and other social networking sites. The rise of "rolls" or individuals who, for personal amusement, post online comments or content that tend to be disruptive, aggressive or inflammatory, in order to provoke a reaction from an audience, accompanied the popularity of social networking.